Decisions in high stress environments - Klein, Gary (Henry Stewart Talks, 2011)
Rational choice decision matrix, Decision strategies used by firefighters, Recognition-Primed Decision (RPD) model, Test of the RPD model, Description of the Naturalistic Decision Making (NDM) community, Intuition and tacit knowledge, Cognitive Task Analysis, Scientific method and NDM research, Aspects of Cognition in natural settings, Applications of NDM